2022
DOI: 10.1088/1752-7163/ac706b
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 RNA load and detection rate in exhaled breath condensate collected from COVID-19 patients infected with Delta variant

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Delta variant is considered responsible for worldwide surges in coronavirus disease 2019 (COVID-19) cases in 2021, with increased infectivity compared to the wild type (Wuhan-1). In a previous study, we identified temporal changes in wild-type SARS-CoV-2 RNA load and detection rate in EBC collected from COVID-19 patients. The primary objective of this study was to clarify temporal changes in Delta-variant SARS-CoV-2 RNA load and detection rates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…It is difficult to conclude which protocol is the most efficient to quantify airborne SARS-CoV-2 RNA levels because different studies have been conducted in different methodological and environmental conditions, as well as in the absence or presence of COVID-19 patients, and among COVID-19 patients with likely different levels of viral shedding [ 16 , 17 ]. For this reason, we selected patients with a recent positive PCR test and the same needs of respiratory support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to conclude which protocol is the most efficient to quantify airborne SARS-CoV-2 RNA levels because different studies have been conducted in different methodological and environmental conditions, as well as in the absence or presence of COVID-19 patients, and among COVID-19 patients with likely different levels of viral shedding [ 16 , 17 ]. For this reason, we selected patients with a recent positive PCR test and the same needs of respiratory support.…”
Section: Discussionmentioning
confidence: 99%
“…The development of procedures to quantify airborne microorganisms is useful for both air control quality and prevention of future infections. The disparity in the results of shedding [16,17]. For this reason, we selected patients with a recent positive PCR test and the same needs of respiratory support.…”
Section: Discussionmentioning
confidence: 99%
“…However, such studies have not been performed, and it is unlikely that they will be, given the complexity of randomizing critically ill patients and strained health care staff as well as the difficulty of attributing health care worker infections to specific exposures given the high prevalence of SARS-CoV-2 in the general community . Similarly, observational studies of the association between SARS-CoV-2 infections among health care workers and exposures to patients receiving HFNO or NIV are complicated by the difficulty of correcting for multiple potential confounders, including patient respiratory disease severity, viral load, quality of room ventilation, duration of health care worker exposure, proximity to patients, and alternative sources of health care worker exposure, including those outside the hospital …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have now demonstrated the presence of the SARS-CoV-2 virus in EBC [14][15][16][17]. Most of these studies are focused on the detection of the viral loads in EBC collected from patients with SARS-CoV-2, but detection rates are widely varied remaining inconsistent and limited [18][19][20]. However, since EBC also reflects the metabolic host response to viral infection, EBC has the potential to mirror those blood metabolic states and its analysis can be used to diagnose, monitor, or detect biomarkers for respiratory illnesses [13,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%